Disturbing the 'spoiled-unspoiled' binary: performances of recovering identities in drug-experienced youths' friendship narratives. (4th May 2019) - Herold, Maria Dich; Søgaard, Thomas Friis
Abstract: In existing recovery studies, binary distinctions between 'spoiled' identities defined by drug-related practices and relationships on the one side, and 'un-spoiled' drug-free identities on the other, are dominant. Similarly, in contexts of youth drug-treatment, substance-using friends are generally viewed as 'bad company', while non-using friends are considered as recovery promoters. This article, however, joins the growing chorus of qualitative researchers beginning to question critically this 'spoiled-unspoiled' distinction. Based on 30 qualitative interviews with 15 young people recruited from a Danish drug-treatment database, we investigate how drug-experienced youth perform recovering identities vis-à-vis their still-using friends. Employing a performative approach to identity formation, we demonstrate how such identity processes play out, and the dilemmas and ambivalences they entail. For example, while drug-using friends are regularly positioned as 'bad company', this is often accompanied by sentiments such as loss and frustration. Our analysis suggests that young people in recovery are easily trapped between societal expectations related to factors such as education on the one hand, and comfortability and connectedness with friends on the other. However, by means of carefully balanced 'borderwork', participants did occasionally manage to integrate using friends into their recovering identities without positioning them as 'bad company' per se. On this basis, we discuss whether breaking bonds with friends who still use drugs is imperative for any process of recovery, and argue that treatment programmes should focus on reconfiguring drug-related friendships, while taking seriously the notion that recovering youth are not necessarily interested in abandoning relations with drug-using friends.